Apramycin resistance plasmids in Escherichia coli: possible transfer to Salmonella typhimurium in calves. - Hunter, J. E. (Cambridge University Press, 1992)
An outbreak of salmonellosis in calves was monitored for persistence of Salmonella typhimurium excretion in faeces and the effect of treatment with apramycin. Prior to treatment apramycin-resistant Escherichia coli were present but all S. typhimurium isolates were sensitive. Following the treatment of six calves with apramycin, apramycin-resistant S. typhimurium were isolated from two treated calves and one untreated calf. Plasmid profiles of E. coli and S. typhimurium were compared and plasmids conferring resistance to apramycin and several other antibiotics were transferred by conjugation in vitro from calf E. coli and S. typhimurium isolates to E. coli K-12 and from E. coli to S. typhimurium. The plasmids conjugated with high frequency in vitro from E. coli to S. typhimurium, and hybridized to a DNA probe specific for the gene encoding aminoglycoside acetyltransferase 3-IV (AAC(3)-IV) which confers resistance to apramycin, gentamicin, netilmicin and tobramycin.